An Efficient, Sustainable Rhodium‐Catalyzed and Ionic Liquid‐Mediated C−H Thiolation and Selenation of Acetanilide with Diaryl Disulfides and Diaryl Diselenides. Issue 4 (24th March 2021) - Rui, Xiyan; Zhu, Yueyue; Dai, Rupeng; Huang, Chaoqun; Wang, Chao; Si, Dongjuan; Wang, Xi; Zhang, Xiaoyuan; Wen, Hongmei; Li, Wei; Liu, Jian
Abstract: We established an efficient and sustainable rhodium(III)‐catalyzed and ionic liquid‐mediated C−S and C−Se formation from readily available starting material acetanilide with diaryl disulfides and diaryl diselenides. The C−H activation proceeds in ionic liquid without extra silver salt as additive, and the catalytic media can be reused for several times to accomplish the catalysts sustainable utilization. Furthermore, this synthesis protocol is suitable for a wide functional group compatibility, and the directing group can be easily removed. Most importantly it can be developed as a facile access to phenothiazine scaffold with potent biological activities, thus this strategy can be broadly applied to organic synthesis and medicinal chemistry. Abstract : An efficient, sustainable rhodium‐catalyzed and ionic liquid‐mediated C−H thiolation and selenation of acetanilide with diaryl disulfides and diaryl diselenides were demonstrated.